Реализация государственной политики в сфере физкультуры и спорта в Приморском крае в послевоенные годы (1946–1953 гг.) - Власов, Сергей Александрович (Гуманитарные исследования в Восточной Сибири и на Дальнем Востоке, 2024)
The article traces the process of implementation of state policy in the field of physical culture and sports in the post-war years (1946–1953) using the case of Primorsky Krai. The author examines the organizational foundations of the state policy aimed at the development of physical culture and sports, the features of its planning, the ways to ensure mass participation of citizens in sports competitions and regular sports activities, as well as the difficulties and problems that challenged the development of physical culture and sports in the region.